Teacher Operant Competences and Organisational Citizenship Behaviour in the Performance of Ugandan Primary Schools - Munene, J.C.; Mulira, F.; Kasekende, F. (Makerere University Business School, 2018)
The study set out to identify a set of functional or operant competences relevant to primary school teaching in Uganda. It was prompted by a need to search for valid teacher practices that can be used as an input in designing an output oriented job description and setting clear performance targets for primary school teachers in the Country. We interviewed ten key teacher informants to generate a set of competence areas referred to as Key Results Areas where each teacher teaching in primary schools must get results. These KRAs were administered in a questionnaire format to three hundred and eighty four primary school teachers and their supervisors who also rated each respondent on a measure of organisational citizenship behaviour. An explanatory factor analysis returned eight interpretable factors which were used as indices for further analysis. A bivariate correlation produced positive correlation between OCB and some of the factors. A multiple regression indicated that operant competences and OCB can predict 25% of the variance in the performance of schools. We recommended a more widespread study of operant competences of primary teachers in preparation for a competence based human resources management i
Keywords: Primary Teachers; Competences; Organisational Citizenship Behaviour; School Performance